The Effect of Oral Stimulation on the Ability to Suck BBLR Babies in the Nicu Room of Toto Kabila Hospital - Sitti Lilimardiani Potabuga; Ani Retni; Rini Asnawati (Universitas Muhammadiyah Palu, 2026)
Babies with BBLR are unable to breastfeed directly from the bottle or breast after birth due to low muscle tone, immature oral motor control, and poor sucking, swallowing, and breathing coordination due to weak sucking reflexes. The purpose of the study was to determine the effect of oral stimulation on the ability to suck BBLR babies in the NICU Room of Toto Kabila Hospital. The quantitative research method with a pre-experiment design is one group pre-test and post-test design, the population of this study is all BBLR babies, the research sample is 18 infants with accidental sampling techniques that meet the sample criteria, the research instrument uses EFS (Early Feeding Skill) observation sheets and oral stimulation SOPs, the data is analyzed with the Wilcoxon test. The results of the study were obtained before being given oral stimulation, the baby's ability to suck was completely devoid of 18 respondents (100%) with an average of 8.78 and after being given oral stimulation, the majority of babies' sucking ability had a suction reflex of 14 respondents (77.8%) and no suction reflex as many as 4 respondents (22.2%) with an average of 11.72, and p-value = 0.000 (? ? 0.05). It can be concluded that there is an effect of oral stimulation on the ability to suck BBLR babies in the NICU Room of Toto Kabila Hospital. Therefore, hospitals are expected to make oral stimulation the standard of nursing care for BBLR babies with suction reflex problems.